A food poisoning caused by ST7 Staphylococcal aureus harboring sea gene in Hainan province, China - Guo, Yahui; Yu, Xiaojie; Wang, Jixiao; Hua, De; You, Yuanhai; Wu, Qingbo; Ji, Qinglong; Zhang, Jianzhong; Li, Liefei; Hu, Yuan; Wu, Zhonghui; Wei, Xiaoyue; et al. (Frontiers in Microbiology, 2023)
ST7 Staphylococcus aureus is highly prevalent in humans, pigs, as well as food in China; however, staphylococcal food poisoning (SFP) caused by this ST type has rarely been reported. On May 13, 2017, an SFP outbreak caused by ST7 S. aureus strains occurred in two campuses of a kindergarten in Hainan Province, China. We investigated the genomic characteristics and phylogenetic analysis of ST7 SFP strains combined with the 91 ST7 food-borne strains from 12 provinces in China by performing whole-genome sequencing (WGS). There was clear phylogenetic clustering of seven SFP isolates. Six antibiotic genes including blaZ, ANT (4′)-Ib, tetK, lnuA, norA, and lmrS were present in all SFP strains and also showed a higher prevalence rate in 91 food-borne strains. A multiple resistance plasmid pDC53285 was present in SFP strain DC53285. Among 27 enterotoxin genes, only sea and selx were found in all SFP strains. A ФSa3int prophage containing type A immune evasion cluster (sea, scn, sak, and chp) was identified in SFP strain. In conclusion, we concluded that this SFP event was caused by the contamination of cakes with ST7 S. aureus. This study indicated the potential risk of new emergencing ST7 clone for SFP.